2022
DOI: 10.7759/cureus.23650
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and the Otolaryngology Match: An Increase in Applicants Remaining Close to Home

Abstract: Introduction: Otolaryngology residency remains one of the most competitive surgical subspecialties to apply for with a 63% match rate in 2021. This is a difficult and stressful process for applicants in any given year, and it was even further complicated by restrictions mandated by coronavirus disease 2019 (COVID-19) protections. Analyzing geographical trends in successfully matched applicants provides prospective applicants and programs with helpful information about how previous trends were affected by the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…This was surprising as previous studies demonstrate the rate of HP matching had a statistically significant increase for other competitive specialties, including plastic surgery (8.3% increase), dermatology (9.1% increase), and otolaryngology (10% increase). [6][7][8][9] Limitations Data were collected from residency program websites and social media accounts, which was the main limitation of this study. Positions that were back-filled, research years, visiting student rotations, and other connections residents may have had to their eventual matched location were also not accounted for.…”
Section: Discussion Key Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This was surprising as previous studies demonstrate the rate of HP matching had a statistically significant increase for other competitive specialties, including plastic surgery (8.3% increase), dermatology (9.1% increase), and otolaryngology (10% increase). [6][7][8][9] Limitations Data were collected from residency program websites and social media accounts, which was the main limitation of this study. Positions that were back-filled, research years, visiting student rotations, and other connections residents may have had to their eventual matched location were also not accounted for.…”
Section: Discussion Key Resultsmentioning
confidence: 99%
“…This was surprising as previous studies demonstrate the rate of HP matching had a statistically significant increase for other competitive specialties, including plastic surgery (8.3% increase), dermatology (9.1% increase), and otolaryngology (10% increase). 6-9…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the beginning of the pandemic, the Association of American Medical Colleges (AAMC) stated that all residency interviews should be transitioned to a virtual platform, which has continued into the 2022-2023 application cycle [7]. Although this change financially benefited applicants, a recent study indicated that otolaryngology applicants who were interviewed virtually were significantly more likely to match within their geographic region as compared to prior to the pandemic [8]. As a result of the numerous changes implemented throughout the COVID-19 pandemic, there was a significant transition to virtual platforms.…”
Section: Introductionmentioning
confidence: 99%
“…T he plastic surgery match in 2021 demonstrated increased matching at home programs, a trend that was reflected in other competitive subspecialties, including otolaryngology and dermatology. [1][2][3] In 2021, there was an 8% increase in home matches. This was thought to be largely due to restrictions in the 2021 cycle; specifically, applicants were not able to do away rotations, and all interviews were performed virtually.…”
mentioning
confidence: 99%